LIVED EXPERIENCES AND ACADEMIC ASPIRATIONS OF AMERICAN CITIZENS LIVING WITH HOME-BASED CARE DUCHENNE MUSCULAR DYSTROPHY PATIENTS - Queddeng, Mercita Q (Journal of Agriculture and Technology Management; Vol 26 No 1 (2023): Vol 26 No 1 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 January - June 2023 Issue, 2023)
The study explores the lived experiences and academic aspirations of the participants living with Duchenne muscular dystrophy (DMD), a rare neuromuscular disorder which could result in an early death due to its progression. This study used the descriptive phenomenology with purposeful sampling in the recruitment of the participants.  A semi-structured interview guide was used and various platforms were considered such as actual interview in actual setting with the inclusion of videoconferencing and telephone interviews in gathering the data needed.  The seven-step method of data analysis of Colizzi was utilized in data analysis in order to derive the themes of this qualitative research. Four major themes emerged that reflected the lived experiences of the American citizens in this study namely: Theme 1: The State of being physically impaired; Theme 2: Support, Social Dependency and Independency; Theme 3: Academic aspirations, Theme 4: Positive Outlook in life and dependable caregivers. The process involves the experiences of the American citizens in the care of DMD patients aside from the dependable medical ventilators and other devises to extend the life span of the Duchenne muscular dystrophy (DMD) patient under their care. Results show positive scenarios of the life experiences of the American citizens with Duchenne muscular dystrophy patients. Despite the enormous demands of their unique task, the participants showed encouraging dispositions (Theme 4:  Positive outlook in life- you can do it, dependable caregiver). Further, it is noted that in spite of these challenges, setting aside the academic aspirations of the patients was never an option.